If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + -5x) + -4 = 10x (1 * 4 + -5x * 4) + -4 = 10x (4 + -20x) + -4 = 10x Reorder the terms: 4 + -4 + -20x = 10x Combine like terms: 4 + -4 = 0 0 + -20x = 10x -20x = 10x Solving -20x = 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -20x + -10x = 10x + -10x Combine like terms: -20x + -10x = -30x -30x = 10x + -10x Combine like terms: 10x + -10x = 0 -30x = 0 Divide each side by '-30'. x = 0.0 Simplifying x = 0.0
| (2a^3b^3+7ab^2)+(5ab^2-2a^3b^3)= | | 8x+5x=104 | | 7x-2x+9+3x+8-5x+6=5 | | x-3(x-12)=26 | | 5(3x+2)=32.5 | | (x-3)(15-6x)=0 | | 17=2x+8 | | x(2x-5)=8 | | 15x-40+21x+18=48x+18-8x-20 | | ax+2=3x+a | | 4x+4=4y | | 12w^4+56w^3+32w^2=0 | | x^4=-25 | | 5x+13=42 | | 4y+10=46 | | 4u^3w^4+12u^9w^6x^9=0 | | 8.7+3.6-5.3= | | 12-10x=80-38x | | 3(4x+5)(3x-2)=0 | | 6(n+4)=8+7n | | 18d-4d-6d-8=2d | | -5m=4m+8 | | 7(m-3)=4(m+3) | | (2x-6)m=26 | | 4(z+2)-2z=10+3(z-3) | | 2(x+7)=40 | | -3.5(4a+1.9)a= | | -3.5(4a+1.9)= | | 4(x-8)=80 | | 8x^2+8x^6= | | (2x+3)(2-3x)-(2-3x)(4x+1)=0 | | y=3x+5y |